Production and Application of Ex-situ Biofloc for Nursery Culture of Pacific White Shrimp Litopenaeus vannamei under Low Salinity Condition - - Nim: 10414024, Haniswita
Pacific white shrimp (Litopenaeus vannamei) is one of the main fishery commodity exports in Indonesia. However, Indonesian shrimp exports are still lower than India, Vietnam, Ecuador, China, and Thailand. This lower export number caused by poor water quality, diseases—including Vibriosis, and the high price of feed which result in high production cost in intensive shrimp culture. Biofloc technology is one of the alternatives to counter the negative side of intensive culture system, however biofloc technology that mostly applied was in-situ biofloc so the component and the function of the biofloc are hard to predict. This study aimed to (1) determine the optimum ratio of biofloc-forming microorganism: Bacillus cereus, Bacillus megaterium, Chaetoceros calcitrans, and consortium of nitrifying bacteria to produce ex-situ biofloc; (2) analyze the effect of biofloc supplementation on the performance of Pacific white shrimp under low salinity; and (3) evaluate microbial community and physiological profile of shrimp supplemented with ex-situ biofloc under low salinity. Three diferent inoculum ratio of B. cereus, B. megaterium, C. calcitrans, and consortium of nitrifying bacteria that was tested are 1:1:6:6 (‘N6’), 1:1:6:9 (‘N9’), dan 1:1:6:12 (‘N12’) and grown at molase and ZA medium. N9 was the selected treatment based on N and P profile, biomass production, and floc porosity through imaging. Then, N9 was used in nursery culture of Pacific white shrimp for 45 days. The experiment consisted of four treatments (1) control treatment without biofloc supplementation (‘K’); (2) 5% (w/w) feed reduction supplemented with 0.3% (v/v) biofloc (‘BF5’); (3) 10% feed reduction supplemented with 0.3% biofloc; and (4) 0.3% biofloc without commercial feed addition (‘BF’). Biofloc supplemental successfully increased the survival and shrimp gained weight of K, BF, BF5, and BF10; 0.86±0.15g, 1.97±0.14g, 1.89±0.29g, and 0.11±0.07g for weight gained and 53.33±5.94%, 51.43±5.71%, 83.81±3.3%, and 85.71±7.56% for survival. Biofloc treatment (BF5, BF10, dan BF10) had higher number of heterotrophic bacteria and lower for total Vibrio. Microbial physiological analysis using BIOLOG EcoPlate that biofloc supplemental could increase the rate of carbon-based substrate degradation. In general, it is suggested that application of ex-situ biofloc can increase shrimp survival and growth most likely due to a more optimal microbial community and physiological profile of the shrimp culture.